Facile synthesis of Ag@Fe3O4/ZnO nanomaterial for label-free electrochemical detection of methemoglobin in anemic patients - Ayub Alam; Batool Fatima; Sameera Shafi; Zohaib Sarwar; Dilshad Hussain; Shan E Zahra Jawad; Saadat Majeed; Muhammad Imran; Muhammad Najam-ul-Haq (Scientific Reports, 2023)
Abstract Methemoglobinemia (MetHb, Fe3+) is a chronic disease arising from the unequal distribution of oxyhemoglobin (HbFe2+, OHb) in the blood circulatory system. The oxidation of standard oxyhemoglobin forms methemoglobin, causing cyanosis (skin bluish staining). Methemoglobin cannot bind the pulmonary gaseous ligands such as oxygen (O2) and carbon monoxide (CO). As an oxidizing agent, the biochemical approach (MetHb, Fe3+) is modified in vitro by sodium nitrite (NaNO2). The silver-doped iron zinc oxide (Ag@Fe3O4/ZnO) is hydrothermally synthesized and characterized by analytical and spectroscopic techniques for the electrochemical sensing of methemoglobin via cyclic voltammetry (CV). Detection parameters such as concentration, pH, scan rate, electrochemical active surface area (ECSA), and electrochemical impedance spectroscopy (EIS) are optimized. The linear limit of detection for Ag@Fe3O4/ZnO is 0.17 µM. The stability is determined by 100 cycles of CV and chronoamperometry for 40 h. The serum samples of anemia patients with different hemoglobin levels (Hb) are analyzed using Ag@Fe3O4/ZnO modified biosensor. The sensor's stability, selectivity, and response suggest its use in methemoglobinemia monitoring.